Is Robot-Assisted Surgery Really Scarless Surgery? Immediate Reconstruction with a Jejunal Free Flap for Esophageal Rupture after Robot-Assisted Thyroidectomy - Seong Hoon Park (Archives of Plastic Surgery, 2017)
Esophageal perforation is a rare but potentially fatal complication of robot-assisted thyroidectomy (RAT). Herein, we report the long-term outcome of an esophageal reconstruction with a jejunal free flap for esophageal rupture after RAT. A 33-year-old woman developed subcutaneous emphysema and hoarseness on postoperative day1 following RAT. Esophageal rupture was diagnosed by computed tomography and endoscopy, and immediate surgical exploration confirmed esophageal rupture, as well as recurrent laryngeal nerve injury. We performed a jejunal free flap repair of the 8-cm defect in the esophagus. End-to-side microvascular anastomoses were created between the right external carotid artery and the jejunal branches of the superior mesenteric artery, and end-to-end anastomosis was performed between the external jugular vein and the jejunal vein. The right recurrent laryngeal nerve injury was repaired with a 4-cm nerve graft from the right ansa cervicalis. Esophagography at 1 year after surgery confirmed that there were no leaks or structures, endoscopy at 1 year confirmed the resolution of vocal cord paralysis, and there were no residual problems with swallowing or speech at a 5-year follow-up examination. RAT requires experienced surgeons with a thorough knowledge of anatomy, as well as adequate resources to quickly and competently address potentially severe complications such as esophageal rupture.